2023
DOI: 10.1021/jacs.3c09904
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Meta-Selective C–H Amination through Non-Covalent Interactions

Qianqian Lv,
Zongxing Hu,
Yousong Zhang
et al.

Abstract: Regioselective C−H amination of simple arenes is highly desirable, but accessing meta-sites of ubiquitous arenes has proven challenging due to the lack of both electronic and spatial preference. This study demonstrates the successful use of various privileged nitrogen-containing functionalities found in pharmaceutical compounds to direct meta-C−H amination of arenes, overcoming the long-standing requirement for a redundant directing group. The remarkable advancements in functional group accommodation for preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Aziridines, recognized as the smallest nitrogen-containing heterocyclic compounds, are a “privileged scaffold” extensively found in natural products and pharmaceuticals, such as Mitomycin A (antitumor agents), Azicemicin A (antimicrobial antibiotic), and FR-66979 (antitumor antibiotic) (Scheme a). Notably, as a crucial building block, various methods for synthesizing aziridines have emerged. These primarily include (1) intramolecular cyclization of amino or azido alcohols, (2) addition of carbene equivalent to imine, and (3) addition of nitrene equivalent to olefin . Transforming simple olefins into high-value-added aziridines, given that the significance of olefins as a chemical feedstock, represents a challenging and significant task.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aziridines, recognized as the smallest nitrogen-containing heterocyclic compounds, are a “privileged scaffold” extensively found in natural products and pharmaceuticals, such as Mitomycin A (antitumor agents), Azicemicin A (antimicrobial antibiotic), and FR-66979 (antitumor antibiotic) (Scheme a). Notably, as a crucial building block, various methods for synthesizing aziridines have emerged. These primarily include (1) intramolecular cyclization of amino or azido alcohols, (2) addition of carbene equivalent to imine, and (3) addition of nitrene equivalent to olefin . Transforming simple olefins into high-value-added aziridines, given that the significance of olefins as a chemical feedstock, represents a challenging and significant task.…”
Section: Introductionmentioning
confidence: 99%
“…Transforming simple olefins into high-value-added aziridines, given that the significance of olefins as a chemical feedstock, represents a challenging and significant task. However, most of the research studies on alkene aziridination have predominantly focused on the syntheses of activated aziridination compounds, where R is an electron-withdrawing group (Scheme b, R = EWG). ,, Typically, these reactions generally require transition metal catalysis. Conversely, the synthesis of free N–H aziridines has garnered relatively less attention, probably due to the scarcity of suitable nitrene precursors and approaches. In a seminal study in 2014, the Kürti, Falck, and Ess group reported a rhodium-catalyzed N–H aziridination of alkenes utilizing O -(2,4-dinitrophenyl)­hydroxylamines (DPHs) as the aminating reagent (Scheme c, left) .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, designs of directing templates based on the distance, conformation, and geometry enabled palladium-catalyzed meta -selective C–H functionalization of benzylamines . In addition, remote meta -selective C–H functionalization of benzylamines has also been achieved through the norbornene relay palladation process, a non-covalent interaction between the substrate and linker, including the use of distal-directing ligands or an organo-initiator . Notwithstanding the vast advance, the success in this field was exclusively limited to ortho - or meta -C–H functionalization, while palladium-catalyzed remote para -C–H functionalization of benzylamines has hitherto not been achieved to date …”
mentioning
confidence: 99%